Flexible Cube Tilt Lattice with Anisotropic Cosserat Effects and Negative Poisson's Ratio. Issue 1 (23rd November 2018) - Rueger, Zach; Ha, Chan Soo; Lakes, Roderic S.
Abstract : A 3D lattice structure consisting of pivoting cubes with flexible links at the corners is presented. It exhibits anisotropic negative Poisson's ratio −0.54 and −0.75. Size effects occur in torsion and bending; these effects are consistent with Cosserat elasticity but not with classical elasticity. Cosserat elastic solids exhibit sensitivity to strain gradients; size effects occur in torsion and bending; also reduction in stress concentrations. The observed Cosserat effects also reveal anisotropy. Abstract : A lattice structure consisting of pivoting cubes with flexible links at the corners are developed. It exhibits negative Poisson's ratio −0.54 and −0.75 in transverse directions. It is therefore anisotropic. Size effects occur in torsion and bending. These effects cannot be understood with classical elasticity but are consistent with Cosserat elasticity. Such effects can reduce stress concentrations hence increase toughness.